Implementasi Di Indonesia Dalam Penghukuman Terhadap Penyalahgunaan Narkoba Perpektif Hukum Islam - Livia, Livia Maylisandi; Syifa Fajastia; Bunga Amalia; Yardah Annissi; Mirale Harahap (Tabayyun : Journal Of Islamic Studies, 2025)
Law No. 35 of 2009 explains that narcotics are substances, synthetic or semi-synthetic drugs derived from plants that can cause loss or alteration of consciousness, numbness, or reduced or eliminated pain. Narcotics crimes are categorized as relatively new offenses that emerged in the modern era. Cases of narcotics abuse in Indonesia continue to increase regardless of age or social background. This law regulates legal sanctions for narcotics offenders, ranging from capital punishment, imprisonment, detention, fines, to medical and social rehabilitation. The imposition of penalties considers juridical aspects, including the fulfillment of charges by the Public Prosecutor, as well as non-juridical factors, which include aggravating and mitigating considerations related to protection.